Brain H+/CO2 sensing and control by glial cells. Issue 8 (1st February 2022) - Gourine, Alexander V.; Dale, Nicholas
Abstract: Maintenance of constant brain pH is critically important to support the activity of individual neurons, effective communication within the neuronal circuits, and, thus, efficient processing of information by the brain. This review article focuses on how glial cells detect and respond to changes in brain tissue pH and concentration of CO2, and then trigger systemic and local adaptive mechanisms that ensure a stable milieu for the operation of brain circuits. We give a detailed account of the cellular and molecular mechanisms underlying sensitivity of glial cells to H + and CO2 and discuss the role of glial chemosensitivity and signaling in operation of three key mechanisms that work in concert to keep the brain pH constant. We discuss evidence suggesting that astrocytes and marginal glial cells of the brainstem are critically important for central respiratory CO2 chemoreception—a fundamental physiological mechanism that regulates breathing in accord with changes in blood and brain pH and partial pressure of CO2 in order to maintain systemic pH homeostasis. We review evidence suggesting that astrocytes are also responsible for the maintenance of local brain tissue extracellular pH in conditions of variable acid loads associated with changes in the neuronal activity and metabolism, and discuss potential role of these glial cells in mediating the effects of CO2 on cerebral vasculature. Main Points: This review article focuses on how glial cells detect and respond to changes in brain tissue pH and concentration of CO2 to trigger systemic and local adaptive mechanisms that ensure a stable milieu for the operation of brain circuits.